Embodied cognition and its significance for education. (March 2019) - Shapiro, Lawrence; Stolz, Steven A.
Psychology has made, and continues to make, a significant contribution to the discipline area of education. Since one of the main aims of education concerns student learning – which is an indisputably psychological phenomenon – we argue that the emerging research agenda of embodied cognition has much to offer educational practitioners, researchers, and/or policy-makers. Although embodied cognition is still in its infancy, the multidisciplinary and interdisciplinary nature of the literature provides some thought-provoking recommendations to enhance educational practice or practices, which in turn can bring about student learning more effectively. Consequently, this article will be concerned with the discussion of two issues: first, we provide a brief historical overview that foregrounds embodied cognition, and, second, we outline the educational implications of embodied cognition through the use of some examples significant to education. We conclude with an argument for the importance of making findings in an area we call 'embodied education' available to teachers.